2023
DOI: 10.1007/s00520-023-07667-w
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination status and attitudes towards COVID-19 vaccination in patients undergoing active cancer treatment in a referral center in Mexico: a survey study

Abstract: Background COVID-19 vaccination refusal/hesitancy among patients with cancer has been reported to be high. This study aimed to assess vaccination status and attitudes towards COVID-19 vaccines in patients with cancer undergoing active treatment in a single center in Mexico. Methods A cross-sectional, 26-item survey evaluating vaccination status and attitudes towards COVID-19 vaccination was conducted among patients undergoing active cancer treatment. Descriptive statistics were used to analyze the sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a study evaluating vaccination status and attitudes towards COVID-19 vaccination among 201 patients undergoing cancer treatment, 95 % of the respondents had received at least one COVID-19 vaccine and 67 % were compliant with WHO guidelines at the time (at least one booster). [27] Nearly a third of the respondents reported “being afraid of side effects” but were not explicitly classified as vaccine hesitant in the study. Moreover, age ≥ 60 years and using mass media as a source of information were highly associated with higher likelihood of having WHO-compliant vaccination status.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study evaluating vaccination status and attitudes towards COVID-19 vaccination among 201 patients undergoing cancer treatment, 95 % of the respondents had received at least one COVID-19 vaccine and 67 % were compliant with WHO guidelines at the time (at least one booster). [27] Nearly a third of the respondents reported “being afraid of side effects” but were not explicitly classified as vaccine hesitant in the study. Moreover, age ≥ 60 years and using mass media as a source of information were highly associated with higher likelihood of having WHO-compliant vaccination status.…”
Section: Resultsmentioning
confidence: 98%
“… nd 50.1 18.8 Villarreal-Garza [28] From 3/12/2021 to 3/26/2021 6/10/2021 540 Women with breast cancer currently living in Mexico Electronic/Snowball 49 [23–85] 100 34 Guaracha-Basáñez [38] From 3/01/2021 to 9/13/2021 12/02/2021 600 Mexican outpatients with a rheumatologic condition, ≥ 18 years Face-to-Face 46 [35–56] 86.5 35.5 Castaneda-Vasquez [33] From 10/2020 to 11/2020 3/23/2021 543 Healthcare Personnel of the State of Nuevo Leon, Mexico Electronic 21 [18–69] 65.0 5.5 Guaracha-Basáñez [39] From 03/01/2021 to 09/30/2021 04/07/2022 1,439 Mexican outpatients with a rheumatologic condition, ≥ 18 years Electronic 47.4ª [nd] 85.8 27.8 González-Block [29] From 12/20/2021 to 12/30/2021 09/192022 360 Community dwellers in Mexico City living with or without comorbidities. Electronic 44.2 [18–86] 50.5 Living with chronic conditions (15 %) Not living with chronic conditions (7 %) Martinez-Cannon [27] From 05/02/2022 to 07/22/2022 03/13/2023 201 Patients with cancer undergoing active cancer treatment in a referral center in Mexico. Electronic 62 [19–92] 57.2 5 Ramonfaur [30] From 09/15/2021 to 10/30/2021 05/03/2023 1,475 Mexican pregnant people attending a follow-up appointment or at labor & delivery at a maternity center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a clear distinction had to be made between COVID-19-related and cancer progression symptoms [ 33 ]. The latter included the clinical manifestations of cancer therapy, in particular of the immuno- and targeted anticancer therapy [ 34 ]. The results have hereby shown partial support for other clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study highlights the critical role of doctors involved in cancer patient treatment, particularly urologists in the case of uro-oncology patients, in promoting COVID-19 vaccination acceptance. Furthermore, Martinez-Cannon et al reported high COVID-19 vaccination rates and positive attitudes among cancer patients in Mexico [ 32 ]. They found that unequivocally supporting information about COVID-19 vaccination in mainstream media and building confidence in vaccine safety were associated with higher vaccination rates in cancer patients.…”
Section: Discussionmentioning
confidence: 99%